IMPROVING STUDENTS’ SPEAKING SKILL BY USINGWORD WALLMEDIA AT THE SEVENTH GRADE STUDENTS OF SMP NEGERI 10 PEMATANGSIANTAR IN THE ACADEMIC 2019/2020 - Tiodora Silalahi; Reni Napitu (Program Studi Pendidikan Bahasa Inggris FKIP, 2021)
In speaking, media are helpful in improving students’ speaking skill. This research is about Improving Students’ Speaking Skill by Using Word Wall Media at the seventh grade students of SMP Negeri 10 Pematangsiantar in the academic year 2019/2020. The material which will be tested is about descriptive text. The students are lack of confidence in speaking English because they think their pronunciation is not good and it makes them difficult to produce meaningful sentences. In this research, the researcher try to apply the Word Wall Media as the media in teaching speaking. The main objectives of this research are to find out the speaking skill of the students after being taught using Word Wall Media. the samples of this research were 14 students of seventh grade. The data were form of quantitative data. The step of research procedure are conducting pre-test, treatment, post-test, and data analysis. The result of the students’ progress during the teaching learning process by using word wall media was good. The finding also proved that in pre-test students average score was 38.571 and post-test score was improved to 81.875 and standart deviation of pre-test score was 3.498 and standart deviation of post-test score was 4.857. It means that the teacher could use Word Wall Media as one of the media in improving students’ speaking skill